Development of artificial neuronal networks for molecular communication - PRINA MELLO, ADRIELE; DELLA CHIESA, ANDREA; BOYLE, NOREEN (My University, 2011)
Communication at the nanoscale can enhance capabilities for nanodevices, and at the same time open new opportunities for numerous healthcare applications. One approach towards enabling communication between nanodevices is through molecular communications. While a number of solutions have been proposed for molecular communication (e.g. calcium signaling, molecular motors, bacteria communication), in this paper we propose the use of neuronal networks for molecular communication network. In particular we provide two design aspects of neuron networks, which includes, (i) the design of interface between nanodevice and neurons that can initiate signaling, and (ii) the design of transmission scheduling to ensure that signals initiated by multiple devices will successfully reach the receiver with minimum interference. The solution for (i) is developed through wet lab experiments, while the solution for (ii) is developed through genetic algorithm optimization technique, and is validated through simulations.
PUBLISHED
Keywords: Neuroscience; Molecular communications; Neuron networks; Nanoscience & Materials; Neuroscience